2010
DOI: 10.1200/jco.2010.28.8415
|View full text |Cite|
|
Sign up to set email alerts
|

Results of the CONFIRM Phase III Trial Comparing Fulvestrant 250 mg With Fulvestrant 500 mg in Postmenopausal Women With Estrogen Receptor–Positive Advanced Breast Cancer

Abstract: Fulvestrant 500 mg was associated with a statistically significant increase in PFS and not associated with increased toxicity, corresponding to a clinically meaningful improvement in benefit versus risk compared with fulvestrant 250 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
257
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 549 publications
(272 citation statements)
references
References 11 publications
(4 reference statements)
9
257
2
4
Order By: Relevance
“…The randomized Phase II Faslodex Investigation of Dose Evaluation in Estrogen Receptor-Positive Advanced Breast Cancer (FINDER) trials 149 and 2,50 carried out in Japanese and non-Japanese patients respectively, compared fulvestrant IAD with LD and HD in postmenopausal women with HR-positive ABC recurring or progressing after prior endocrine therapy, reporting a trend toward improved efficacy with HD and LD compared to the IAD. They set the ground for the large confirmatory Phase III study Comparison of Fulvestrant In Recurrent or Metastatic Breast Cancer (CONFIRM), comparing fulvestrant HD versus the IAD in 736 postmenopausal women with ER-positive ABC who experienced disease progression during adjuvant or first-line endocrine therapy or within 1 year from completion of adjuvant endocrine therapy, about two-thirds of whom had acquired endocrine resistance and a third had primary resistance 65. PFS was significantly longer with the HD compared to the IAD (hazard ratio 0.80, 95% CI 0.68–0.94; P =0.006).…”
Section: Efficacy Studies For Fulvestrant As Monotherapy or In Combinmentioning
confidence: 99%
See 2 more Smart Citations
“…The randomized Phase II Faslodex Investigation of Dose Evaluation in Estrogen Receptor-Positive Advanced Breast Cancer (FINDER) trials 149 and 2,50 carried out in Japanese and non-Japanese patients respectively, compared fulvestrant IAD with LD and HD in postmenopausal women with HR-positive ABC recurring or progressing after prior endocrine therapy, reporting a trend toward improved efficacy with HD and LD compared to the IAD. They set the ground for the large confirmatory Phase III study Comparison of Fulvestrant In Recurrent or Metastatic Breast Cancer (CONFIRM), comparing fulvestrant HD versus the IAD in 736 postmenopausal women with ER-positive ABC who experienced disease progression during adjuvant or first-line endocrine therapy or within 1 year from completion of adjuvant endocrine therapy, about two-thirds of whom had acquired endocrine resistance and a third had primary resistance 65. PFS was significantly longer with the HD compared to the IAD (hazard ratio 0.80, 95% CI 0.68–0.94; P =0.006).…”
Section: Efficacy Studies For Fulvestrant As Monotherapy or In Combinmentioning
confidence: 99%
“…The CONFIRM study65 reported the following grade 1–4 AEs with fulvestrant HD: gastrointestinal 20.2%, joint disorders 18.8%, injection-site reactions 13.6%, hot flashes 8.3%, urinary tract infection 2.2%, ischemic cardiovascular disorders 1.4%, thromboembolic events 0.8%, vaginitis 0.8%, osteoporosis 0.3%, and weight gain 0.3%. Grade ≥3 AEs were gastrointestinal disturbances 2.2%, joint disorders 2.2%, thromboembolic events 0.6%, injection-site reactions 0.3%, and urinary tract infection 0.3%.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…If the cancer progressed on therapy with non-steroidal AI (letrozole or anastrozole) or if an AI therapy was terminated less than 1 year ago, two distinct options for endocrine treatment may be considered, i.e. (i) fulvestrant (500 mg every 4 weeks) [9] or (ii) a combination of exemestane plus everolimus [10] (fig. 2).…”
Section: Endocrine and Targeted Therapy In Metastatic Breast Cancermentioning
confidence: 99%
“…The neoadjuvant NEWEST trial [6] showed significantly greater biological activity benefit with high-dose fulvestrant compared to the approved dose. The randomized, double-blind CONFIRM (Comparison of Faslodex in Recurrent or Metastatic Breast Cancer) trial presented recently [7] has shown a small but statistically significant increase in time to progression for fulvestrant 500 mg compared with fulvestrant 250 mg, without increase of toxicity.…”
Section: Introductionmentioning
confidence: 99%